Aerodigestive disorders in dogs evaluated for cough using respiratory fluoroscopy and videofluoroscopic swallow studies. (September 2019) - Grobman, M.E.; Masseau, I.; Reinero, C.R.
Highlights: Videofluoroscopic swallow study (VFSS) abnormalities were found in 81% of dogs with cough and no alimentary signs. Eighty two percent of dogs with unremarkable radiographs had VFSS abnormalities. VFSS abnormalities were found in 6/7 dogs with laryngeal paralysis. Pathologic reflux was found in 36% of dogs with abnormal VFSS. Abstract: Aerodigestive diseases, hybrid disorders representing a pathologic link between respiratory and alimentary tracts, may manifest with respiratory signs without gastrointestinal signs. These are underdiagnosed in dogs due to poor clinical recognition and diagnostic limitations. We hypothesize that a subset of dogs presenting for cough without gastrointestinal signs would have occult aerodigestive disorders identified using videofluoroscopic swallow study (VFSS). Data were retrospectively obtained from 31 client-owned dogs presenting for cough, with thoracic radiographs, and a VFSS between April 2015 and December 2017. Exclusion criteria were cough of cardiac origin or gastrointestinal signs within 6 months. Swallow study parameters included pharyngeal/esophageal motility, laryngeal obstruction/defects, penetration–aspiration, reflux, excessive aerophagia, megaesophagus (ME), lower-esophageal sphincter achalasia-like syndrome (LES-AS), and sliding hiatal hernia (HH). The median (interquartile range) duration of cough was 4 (2–8) months. Thoracic radiographs were unremarkable in 11 dogs, with aspiration pneumonia suspected in seven. In 25/31 dogs (81%), VFSS abnormalities were detected and some dogs had more than one defect: pharyngeal ( n  = 10) or esophageal hypomotility ( n  = 10), reflux ( n  = 9), penetration–aspiration ( n  = 8), excessive aerophagia ( n  = 6), laryngeal obstruction ( n  = 3), ME ( n  = 3), HH ( n  = 2), and LES-AS ( n  = 1). A respiratory disorder causing cough was identified in 17 dogs with VFSS abnormalities (laryngeal obstruction/defect and airway disease including chronic or eosinophilic bronchitis, tracheal/mainstem bronchial collapse, bronchiectasis, and bronchomalacia). An alimentary disorder identified on VFSS in absence of a discrete respiratory disorder causing cough was diagnosed in eight dogs. In conclusion, canine aerodigestive disorders can manifest as cough without alimentary signs. VFSS is a useful diagnostic to determine the contribution of esophageal/gastrointestinal pathology in dogs with cough.